2017
DOI: 10.1039/c7md00475c
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of hydrophobic and hydrophilic bile acids in angiogenesis usingin vitroandin vivomodel systems

Abstract: Bile acids have emerged as strong signaling molecules capable of influencing various biological processes like inflammation, apoptosis, cancer progression and atherosclerosis depending on their chemistry. In the present study, we investigated the effect of major hydrophobic bile acids lithocholic acid (LCA) and deoxycholic acid (DCA) and hydrophilic bile acids cholic acid (CA) and chenodeoxycholic acid (CDCA) on angiogenesis. We employed human umbilical vein endothelial cells (HUVECs) and zebrafish embryos as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Kundu et al evaluated the ability of non-conjugated bile acids to alter angiogenesis in in vitro and in vivo studies [ 28 ]. They found that the hydrophobic bile acids deoxycholic acid (DCA) and LCA inhibited tube formation and cell migration in human umbilical endothelial cells (HUVECs) in vitro, but LCA was cytotoxic to cells and could only be studied at lower, non-lethal concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kundu et al evaluated the ability of non-conjugated bile acids to alter angiogenesis in in vitro and in vivo studies [ 28 ]. They found that the hydrophobic bile acids deoxycholic acid (DCA) and LCA inhibited tube formation and cell migration in human umbilical endothelial cells (HUVECs) in vitro, but LCA was cytotoxic to cells and could only be studied at lower, non-lethal concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophilic bile acids CA and CDCA had differing effects on angiogenesis. CA had no effect on angiogenesis in vitro, while CDCA actually induced angiogenesis in vitro and in zebrafish [ 28 ]. Our studies have shown that taurine and glycine conjugates of CA inhibit in vitro CEC migration and tubulogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also demonstrated that CDCA increased the expression levels of flTF and asTF in EA.hy926 cells, which indicated that CDCA may be associated with vasoconstriction. Furthermore, Kundu et al (9) demonstrated that CDCA is capable of promoting vessel formation. In a previous study, both variants were revealed to mediate various physiological and pathological functions, including angiogenesis (2).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids are strong signaling molecules that are capable of influencing various biological processes, including inflammation, apoptosis, cancer progression and atherosclerosis. Chenodeoxycholic acid (CDCA) is a bile acid that has been demonstrated to enhance ectopic vessel formation (9). Similarly, apolipoprotein M (apoM), which was discovered by Xu and Dahlbäck in 1999 (10), is mainly located in high-density lipoprotein in the blood and has been demonstrated to be associated with tumor growth, atherosclerosis and thrombosis (1113).…”
Section: Introductionmentioning
confidence: 99%
“…This fact is exploited in targeting drugs to cancerous tissues The biological functions of bile acids depend on their chemical nature and polarity [8]. Both LCA and deoxycholic acid (DCA) are hydrophobic but show different toxicity [9]. Bajaj et al [10] have reported that DCA having two hydroxyl groups shows weak interactions with cell membranes compared to highly hydrophobic LCA.…”
Section: Introductionmentioning
confidence: 99%